Late Quaternary Climate Reconstruction and Lead-Lag Relationships of Biotic and Sediment-Geochemical Indicators at Lake Bolshoe Toko, Siberia ... - Biskaborn, Boris K.; Nazarova, Larisa; Kröger, Tim; Pestryakova, Luidmila; Syrykh, Liudmila; Pfalz, Gregor; Herzschuh, Ulrike; Diekmann, Bernhard (Humboldt-Universität zu Berlin, 2021)
Millennial-scale climate change history in eastern Siberia and relationships between diatom diversity, paleoclimate, and sediment-geochemical lake system trajectories are still poorly understood. This study investigates multi-proxy time series reaching back to the Late Pleistocene derived from radiocarbon dated Lake Bolshoe Toko sediment cores, southeastern Yakutia, Russia. We analyzed diatoms, elements (XRF), minerals (XRD), grain-size, organic carbon, and included chironomid analyses and published pollen-data for quantitative paleoclimate reconstruction. Changes in diatom species abundances reveal repeated episodes of thermal stratification indicated by shifts from euplanktonic Aulacoseira to Cyclotella species. Chironomid and pollen-inferred temperature reconstruction reveal that the main shift between these diatom species is related to the onset of Holocene Thermal Maximum (HTM) at 7.1 cal ka BP. Comparison to other paleoclimate records along a north-south transect through Yakutia shows that the HTM was ...